(untitled) (Malaysian Journal of Civil Engineering, 2018)
The Structural Health monitoring with Schmidt Rebound Hammer is being widely used by many consultants. The rebound hammer is use for Concrete structures for predicting the service life. The present research work attempted to interpret different Concrete mix designs by Surface hardness method, which gives a test method for structural health assessment by a suitable correlation between Rebound hammer number and Concrete compressive strength. Thus, the objectives of this present research are threefold. First, this research will examine the influence of conditioning such as drying condition on the results of Schmidt hammer test performed on Concrete cubes with different Mixtures proportion. In which W/C ratio, Slump, Grade of concrete, Fine aggregate, Coarse aggregate, Cement content, and Water content under two different conditions such as Slump, and W/C ratio value was varied with constant Compressive strength as in the First case and Compressive strength, and W/C ratio value varied with constant Slump as in the Second case. Seventy-two concrete cubes (100 mm3) with Grades of concrete ranges from 25 to 40 N/mm2 were prepared and tested using Schmidt Rebound hammer equipment. The non-destructive test parameters were relate to different Mixtures proportion in ordered to characterize Mix designs. Second, this research will examine the influence of the hardness value on compressive strength. Third, this research will also aims to develop non-destructive charts for different concrete mixtures proportion. Thus, the Schmidt hammer test due to the developed chart gave a better value. This implied that the developed chart was more suitable for normal strength concrete as well as minimising inaccuracy in non-destructive tests.